Ipilimumab-Induced Neutropenia in Melanoma - Makiko Ban-Hoefen MD; Richard Burack MD; Lynn Sievert NP; Deepak Sahasrabudhe MD (SAGE Publishing, 2016)
Ipilimumab is a human monoclonal IgG1 antibody against CTLA-4 that has been shown to prolong the overall survival of advanced melanoma. The most common adverse events associated with ipilimumab are immune-related. Severe hematological toxicity is rare. We report a case of severe neutropenia following ipilimumab therapy that fully resolved after the administration of prednisone, cyclosporine, and anti-thymocyte globulin therapies.